Size-Selective Sieving for Detecting Teliospores of Tilletia indica in Wheat Seed Samples - Peterson, G L (Plant disease, 2000)
A method was developed to isolate teliospores of Tilletia indica from infested grain. The technique was evaluated to determine its sensitivity for detection and quantification of teliospores, the time required to conduct an individual test, and its utility for the detection and identification of the pathogen for phytosanitary regulation and seed certification. A seed wash of a 50-g grain sample was washed through 53-μm and 20-μm pore size nylon screens to remove unwanted debris and to concentrate and isolate teliospores. The material retained in the 20-μm screen was suspended for direct microscopic examination or plated on water agar for teliospore germination and identification by polymerase chain reaction (PCR) utilizing two pairs of T. indica-specific primers. The reliability of detection for both light microscopy and PCR are 100% at an infestation of five teliospores per 50-g sample. The proportion of teliospores recovered from grain samples artificially infested with T. indica was 0, 82, 88, 81, and 82%, respectively, at infestation levels of 0, 1, 2, 5, and 10 teliospores per 50-g wheat sample. Extraction efficiency was comparable to the centrifuge seed-wash method currently used by most seed health laboratories. Sample analysis using size-selective sieving was more than 83% faster than the standard centrifuge seed wash